THE INFLUENCE OF TRUST LEVEL, CONSUMER SATISFACTION AND PRICE REGARDING CAT PURCHASING DECISIONS ON FACEBOOK MARKET PLACE - Talita Ainun Nursalsabillah C; Rahmaniar; Ikramuddin; Syamsul Bahri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to see the influence of the level of trust, consumer satisfaction and price on the decision to purchase cats on the Facebook Market Place. The sampling technique in this research is Purposive Sampling. The sample in this study was 160 consumers who purchased or adopted cats on the Facebook market place. Primary data in this research was taken by distributing questionnaires, the analytical tools used were multiple linear regression analysis methods, classical assumption tests, instrument tests (validity and reliability), hypothesis testing and coefficient of determination using the SPSS version 29 program. The results of this research show that the trust variable (X1) has a significant positive effect on purchasing decisions (Y), the consumer satisfaction variable (X2) has a significant positive effect on purchasing decisions (Y) and the price variable (X3) has a significant positive effect on purchasing decisions (Y). It can be concluded that the influence of each variable simultaneously can be seen that the significance value is 0.001 < 0.05 and the value of Fcount is 22,676 > Ftable 2.12. The data was processed statistically using SPSS version 29 program tools. The Adjusted R square value is 0.290 or 29.0%, which means that variations in the independent variables trust, consumer satisfaction and price, can explain the purchasing decision variable by 29.0%, while the remainder is 71.0% explained by other variables not examined in the research. The Managerial implementation in this research shows that increasing trust, consumer satisfaction and price influence the decision to purchase cats on the Facebook market place.